(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The main character in geological structure of copper-porphyritic Kashen deposit belongs to Mesolithic (middle Jurassic, Bathonian age) pyritized secondary quartzites, the origin of which is due to hetero-volcanic fumaroles-solfataric acid gas-water solutes. Copper mineralization is located on the rocks of secondary quartzite formation. In Kashen ore field sericite face of quartzite is exclusively developed. Inner facies are characterized by secondary quartzite-kaolinite, alunite, monoquartzite, sulphur opalite absence in the ore field. Due to fumaroles-solfataric theory these types of quartzite had to be located upper than sericitized quartzite in the higher levels closer to volcanic caldera, but they were not preserved, because of being eroded during more than 170 million years.